Gendered transformations: rethinking climate resilience building in northwest Ghana - Osei-Amponsah, Charity; Okem, Andrew; Wahabu, E.; Quarmine, William; Hyde, Sandra N. T. (Springer, 2025)
The transformation of gender roles and responsibilities have implications for how men and women and other social groups are impacted by and cope differently with the changing climate. However, such dynamics are often not considered in formulating and implementing climate resilience interventions. Through a case study in rural communities of the northwestern part of Ghana, Africa, using a mixed-methods approach, this paper investigates the gendered nature of transformations and the implications for climate resilience building. The study found that compared to ten years ago, women have increase access to farmland, participate more in agricultural development decision-making, better access to credit, and more diverse livelihood pathways. Nevertheless, women’s ability to adapt to climate change impacts like droughts is worsening because of cultural norms that restrict women’s control over land resources and their limited adaptive capacities. To achieve positive gendered transformation outcomes while minimising negative social transformation trade-offs, policy makers must rethink the strategies for building climate resilience. There is the need to focus on strategies that support the formulation and implementation of well-funded and targeted interventions with a perspective on gender realities and dynamics that provide women with real resources and agency, enabling institutional support and transformative opportunities.